Peran Kepemimpinan Dalam Meningkatkan Kinerja Tim - Mursyid Choirullah; Al Hilal Ramadhan (Pusat Riset dan Inovasi Nasional, 2024)
Leadership, described as a leadership style that can arouse or motivate employees, so that they can develop and achieve performance at a high level beyond what they previously expected. The method for writing this scientific article is by literature study or library search. Examining journals that are in accordance with the theory discussed, research results from several research journals show that transformational leadership has a significant positive impact on team performance.